Fiscal Policy and Development : Human, Social, and Physical Investments for the SDGs - Gaspar, Vitor (Staff Discussion Notes; Staff Discussion Notes, 2019)
The goal of this paper is to estimate the additional annual spending required for meaningful progress on the SDGs in these areas. Our estimates refer to additional spending in 2030, relative to a baseline of current spending to GDP in these sectors. Toward this end, we apply an innovative costing methodology to a sample of 155 countries: 49 low- income developing countries, 72 emerging market economies, and 34 advanced economies. And we refine the analysis with five country studies: Rwanda, Benin, Vietnam, Indonesia, and Guatemala.